Israel approaches the nuclear threshold: the controversies in the American administration surrounding the Israeli nuclear bomb 1968–1969. Issue 5 (2nd September 2016) - Gutfeld, Arnon
ABSTRACT: The article focuses on the internal debate in the US Administration as Israel Approached and passed the Nuclear threshold in 1968–1969. The article is based on recently released American Defense and State Departments documents and also on Presidential and National Security Advisor documents hitherto unavailable.